Combining transcriptomics and proteomics to unveil possible PROP1 interactors during embryonic pituitary development - Iglesias García, Lucía Candela (2024)
Congenital hypopituitarism (CH) is a deficiency of one or more hormones produced by the anterior pituitary. The most frequently mutated gene in CH is PROP1, which has a very dynamic expression pattern. In Prop1 mutant mice, the pituitary is dysmorphic, with increased apoptosis and abnormal vascularization. These mutant mice are dwarfs and develop hypopituitarism. In previous work we have shown that PROP1 has a key role in stimulating progenitors to undergo an EMT-like transition before differentiation.